MASYARAKAT MANDAILING DI NAGARI INDERAPURA SELATAN KABUPATEN PESISIR SELATAN 1973-2010 - WARNI, ERMA - (Pendidikan Sejarah, 2014)
This thesis aims to describe the social and cultural changes that are Mandailing Kampung Sungai Kuyung Nagari Inderapura Selatan Kecamatan Of Pancung Soal 1973-2010 were revealed from the point of hisyory. The formulation of the problem in this study is as follows : Describe the social life at Mandailing Inderapura Selatan and describe the cultural life of the community Mandailing in Inderapura Selatan.This thesis aims at how socio-cultural community Mandailing in Kampung Sungai Kuyung. Writing method used is the historical method to phases: (1) heuristics are searching for and collect information from primary and secondary sources(2) criticism of sources including internal and external criticism, namely the testing of the authenticityand validaty of the information , (3) interpretation of interpreting and connecting the existing facts. (4) Historiography ie the presentation of research result in the from of thesis.The result show that social LIfe Mandailing in 1973-2010 Kampung Sungai Kuyung Nagari Inderapura Selatan have ups and downs in which the early 1990s but has not been seen for social change in the 2000s increased social field when viewed from the income, education and activity social. In multiethnic societies Mandailing to enforce social control so that the sosial relations that occur (social interaction) can run well and harmoniously, as a manifestation of social control in the midst of peoples lives in Nagari Inderapura selatan geverm,ants established certain intitutions that server as a controller in order not occur various clashes between tribes.